On the importance of affective dimensions of mathematics education - Pieronkiewicz, Barbara (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2014)
In one of his latest articles, Fortus (2014), points out that “when one considers the centrality of affect to teaching and learning and the broad range of topics that are related to affect, it is concerning that it has received relatively so little attention” (Fortus 2014, p. 821). In order to support his position, he provides an overview of the research on affect in science education that has been published in several journals (JRST, SciEd, and IJSE) between 2001 and 2011. The author also hypothesizes why affect has been under-attended to by the science education research community so far. And the conclusion he arrives at is that affect remains in the shadow of researchers’ attention partly due to the existing “international trend towards standardization of schooling and high-stakes testing” (p. 822). The main purpose of this article is to emphasize that affect does play an important role also in learning mathematics and for this reason it should be considered as one of the core dimensions of mathematics education.
Didactics of Mathematics, 2014, Nr 11 (15), s. 13-24
Keywords: affect in mathematics education; math anxiety; underachievement syndrome